2018
DOI: 10.1177/1541931218621442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of Distraction Detection Algorithms on Multiple Data Sources

Abstract: Many researchers have developed algorithms to detect distraction, but they have yet to be validated on multiple data sources. This study aims to evaluate these algorithms by comparing their ability to detect distraction and predict event likelihood. Four algorithms that use measures of cumulative glance, past glance behavior, and glance eccentricity were used to understand the distracted state of the driver and were validated on two separate data sources: naturalistic and experimental data. Results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The eye glance data were coded and analyzed for this study by primary and secondary coders who were knowledgeable about the process of identifying a glance location. The eye glance data was also analyzed in the context of evaluating distraction detection algorithms, which is included in a separate study (Mehrotra et al, 2018).…”
Section: Equipmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The eye glance data were coded and analyzed for this study by primary and secondary coders who were knowledgeable about the process of identifying a glance location. The eye glance data was also analyzed in the context of evaluating distraction detection algorithms, which is included in a separate study (Mehrotra et al, 2018).…”
Section: Equipmentmentioning
confidence: 99%
“…Past research has found positive influence due to passenger intervention (Buckley & Davidson, 2013), as well as acceptability of negative norms by peers resulting in negative influence (Chein et al, 2011). Research by Zhang et al, (2018) examined this degree of association through measures of stimulating companionship. These studies point toward the degree of relationship between driver and passenger as having a variable impact on behavior.…”
Section: Use Of Eye Glances To Understand Driving Behaviormentioning
confidence: 99%
See 3 more Smart Citations